عبادات سے متعلق احیاء العلوم میں بیان کردہ تفسیری اقوال کا تجزیاتی مطالعہ: An Analytical Study of Tafsir Sayings Explained in Ahya Al-Uloom regarding Ibadat - Muhammad Siddique; Fraz Ahmed; Dr. Hafiz Asif Mehmood (International Research Journal of Arabic and Islamic Studies, 2023)
In the Quran, "libasan" refers to physical clothing, "risha" to adornment, and "libas al-taqwa" to the inner garment of modesty and piety. According to Imam Ghazali, Allah has provided both physical attire and the inspiration for inner piety. For gaining knowledge, it is essential for the heart to be cleansed of bad morals, as knowledge is a form of worship and a means of drawing closer to Allah. "Kun fayakoon" illustrates God's creative power, where His will instantly brings things into existence. Prayer is a fundamental pillar of Islam, embodying worship, servitude, and unity, and the call to prayer (Adhan) announces the congregational prayer. Charities and zakat should be given publicly to encourage others, and the true deserving are those who do not ask. In Hajj, offering a fine animal for sacrifice is crucial for piety, not for show. Recitation of the Quran should be done with ablution, respect, and tranquility. According to Hazrat Ali, recitation while standing is the most virtuous.